Labia minora necrosis secondary to bilateral Bartholin cyst resection: a case report - Moreno, Karla Durán; Martínez Cabrales, Filiberto; Rivas Penilla, Luisa Fernanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This is a case report of a necrosis of labia minora secondary to bilateral Bartholin cyst resection. A 48-year-old woman with history of bilateral Bartholin cyst resection in the previous month, she presented a discontinuity of the right labia minora in its upper segment of 2x3 cm, she reported no pain or discomfort, no dyspareunia. A labiaplasty with edge resection technique was performed there were no signs of hematoma or any complications in the procedure. In a 3 month follow up we observed a resolution of necrosis, no dyspareunia and had adequate aesthetic results. This is a rare complication in large Bartholin gland cysts, there is scarce literature about it and there is no evidence as to which labiaplasty technique is superior in the case of this complication. We present an option of treatment in a labia minora necrosis due to a surgical complication.